Digital design for print and web : an introduction to theory, principles, and techniques - DiMarco, John, 1969- 4 0 16; 5 (Hoboken, NJ : Wiley, 2010)
Explains the basic theories, concepts and principles of digital design for print and Web sites, providing illustrated step-by-step instructions for techniques with professional examples, and discussing Adobe Creative Suite software applications. Includes information to access online content.
Includes bibliographical references and index.
Adult;Adult
Keywords: 2 -- 0; 6; Data processing.;Data processing.;Design.;Data processing.;Data processing.;Design. -- Commercial art;Graphic arts;Web sites;Commercial art;Graphic arts;Web sites; 20; 2